Particle transport simulations based on selfconsistency of pressure profiles in tokamaks - Danilov, A.V.; Dnestrovskij, Yu. N.; Andreev, V.F.; Cherkasov, S.V.; Dnestrovskij, A.Yu.; Lysenko, S.E.; Vershkov, V.A. (Вопросы атомной науки и техники, 2006)
Simulation of particle and heat transport was performed with the ASTRA code. The equations for the electron
temperature and density, ion temperature and current diffusion were solved. For the heat transport we used the
canonical profiles model. Three T-10 pulses with toroidal magnetic field 2.5 T, plasma current 250…255 kA, initial
average density 1.3, 2.4 and 3.2×10¹⁹ m⁻³ respectively, on-axis 900 kW ECRH and D₂ puffing were considered. The
model proved to describe rather fast penetration of the density disturbance from the edge to the core during 15…20 ms
after gas puffing. The simulation of the density profiles agrees with experiment in Ohmic and ECRH phases, and during
the gas puffing, describing the particle pump-out after ECRH switch-on. The neutral influx at the plasma edge increases
after ECRH switch-on in agreement with Da measurements. Both the effective diffusion coefficient and pinch velocity
decrease slightly when the plasma density is increased. A set of two Ohmic and three NBI MAST pulses were
considered for comparison.